Pottery Clay: An Aid to Stabilize the Metal Components During Soldering. Issue 4 (October 2021) - Ram, RSVM Raghu; Ranganayakulu, I; Viswanadh, K Anand
Lack of stabilization of metal components during soldering is the most common problem encountered in orthodontic lab work. Metal components tend to slip or change from their actual position during soldering. This article provides a simple tip for easy and steady positioning of metal components during the soldering procedure using pottery clay.